Ijtihad, Patterns, Orientation, and the Need For It - Jibril Adam Harahap; Deni Afriansyah (AT-TAFAHUM: Journal of Law, 2024)
Ijtihad is an important concept in Islamic law which means the serious deployment of all intellectual abilities to find the law on issues not explicitly explained in the Qur'an and Al-Sunnah. Terminologically, ijtihad is understood as the use of independent legal reasoning to answer new problems while remaining based on the primary sources of sharia. Ijtihad plays an important role in the process of interpreting religious texts so that Islamic law can be applied relevantly in concrete situations of human life. In practice, ijtihad has several main patterns, namely the bayani pattern which emphasizes the linguistic analysis of the text, the ta'lili pattern which focuses on finding 'illat or legal reasons through rational reasoning, and the istislahi pattern which prioritizes the welfare of the people based on the principles of daruriyyat, hajiyyat, and tahsiniyyat needs. In addition to patterns, there are also orientations of ijtihad such as textual, analogical, benefit, maqashid sharia, and renewal (tajdid) approaches which show the dynamics of the methods of developing Islamic law.